Digital India: Opportunities and Challenges - Thakur, Payal; Rangra, Kalpana (International Journal of Computer Sciences and Engineering, 2025)
The society and individuals who acquire skills and increase their technological information are able to analyze the data generated and acquire information of digital environment to enter into a higher economic stratum. The one who enhance the skills are vibrant and inspirational in society while those who remain illiterate digitally are being pushed down the ladder and have to invest hard in terms of money and knowledge for their successive and progressive growth. To get along with the advancement and enhancement of technology the political system has to adjust itself and proceed in tandem dynamically. The adaption of encouraged technological advancement in the field of computer systems and relative areas has given immense impetus to economical growth of company. Digital India programme is an effort in this idea. The presented work reviews the programme and various issues that have addressed along with the implementation and challenges.